Naoxintong Is Involved in the Coagulation Regulation of Warfarin Through the MAPK Pathway - Luo X; Chen L; Xu J; Li J (Pharmacogenomics and Personalized Medicine)
Xiao Luo,1,2,* Ling Chen,2,* Jingsong Xu,1 Juxiang Li1 1Department of Cardiovascular Medicine, The Second Affiliated Hospital, Jiangxi Medical College, Nanchang University, Nanchang, Jiangxi, 330000, People’s Republic of China; 2Department of Cardiovascular Medicine, Jiujiang City Key Laboratory of Cell Therapy, Jiujiang No. 1 People’s Hospital, Jiujiang, Jiangxi, 332000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Juxiang Li, Department of Cardiovascular Medicine, The Second Affiliated Hospital, Jiangxi Medical College, Nanchang University, No. 1, Minde Road, Donghu District, Nanchang, Jiangxi, 330000, People’s Republic of China, Tel +86 15707923841, Email ndefy87008@ncu.edu.cnObjective: To explore the effect of Naoxintong (NXT) on warfarin anticoagulation therapy and its potential mechanism.Methods: TCSMP, SwissTargetprediction, SuperPred, SEA, and Batmanic-TCM were used to search for active ingredients and targets of NXT and warfarin; the DisGENT database was used to find disease targets of coagulation disorders. Cytoscape software was applied to construct the “drug-target”network; the protein interaction network (PPI) was used to study the protein-protein interaction. GO and KEGG were used for functional analysis. The effect of NXT on warfarin anticoagulation was then tested in rats by analyzing coagulation factors in blood before and after drug administration. The expression of MAPK in the liver tissue was determined by Western blot.Results: The top five components of NXT affecting warfarin anticoagulation degree value were MOL000098, MOL000422, MOL000006, MOL000358, and MOL000449. TP53, AKT1, SRC, TNF, HSP90AA1, STAT3, JUN, IL6, EGFR, and ESR1 were the core targets of NXT, while MAPK9, MAP3K5, MAPK8, and MAPK1 in the MAPK family were important targets of NXT in the coagulation process. In vivo testing indicated that NXT may be able to participate in the regulation of the warfarin coagulation process through multiple targets and multiple pathways, which may be related to MAPK.Conclusion: Our data suggests that NXT is involved in the coagulation regulation of warfarin through the MAPK pathway.Keywords: Naoxintong, Warfarin, coagulation dysfunction, network pharmacology, mechanism research